BIOGEOGRAFIA DE LOS ICHNE UMONIDAE CHILENOS (HYMENOPTERA: ICHNEUMONIDAE) - Porter, Charles C. (Acta Entomológica Chilena, 2022)
from the 24lh to the 18lh parallel (continuing northward almost to the equator as the Peruvian Coastal Desert and Precordillera) and (2). The Neantartic Realm including all Chile south of the 25lh parallel as well as a narrow strip of western Argentina south or the 38,h parallel. Below 3000 m, the Northern Province is an almost absolute desert, where life is confined to river valleys and oases. These lowland refugia are inhabited by a depaupérate biota with few endemic but many Neotropic, Andino-Patagonian, and Cosmopolitan genera although with numerous endemic species. Between 2000-3500 m most of the Neotropic genera disappear, but from 3000 m to the showline annual precipitation increases and allows development of a diverse Andino-Patagonian flora and fauna similar to that of the central Andes in Perú and Bolivia but with a large component of endemic species and subspecies. The Neantarctic Realm embraces habitats from semidesert in the north through sclerophyll woodland at intermediate latitudes to humid Nothofagus Forest below the 38lh parallel. The Neantarctic biota differs strongly from that in the rest of South America and can not be included as a subelement of the Neotropic. It has 121 ichneumonid genera of which 39 (32%) are endemic, 31 (26%) Cosmopolitan, 20 (16.5%) Holarcticor Holarctic-Oriental, 17 (14%) Neotropic, 8 (6.6%) Andino-Patagonia with frequent representation in the Coastal mountains of south Brasil, 4 (3,3%) transantarctic with species in Neantartic Chile as well as in Australia and sometimes also New Zealand, and with 3 genera (2.4%) widely but disjunctly distributed in both the Northern and Southern Hemispheres. Clearly, the outstanding anomalies of the Neantarctic ichneumonid fauna are its exceptionally high number of endemic genera and its surprisingly few Neotropic genera for an area in geographic proximity to the American Tropics. It is hypothesized that the main lineages within the Ichneumonidae were already present in the Cretaceous, at a time when the world’s continents were still united by land bridges and the global climate was rather uniformly humid and much warmer than at present. A diverse biota evolved on Antartica at this time and was extensively shared with Southern South America and Australia up to the Eocene. The aberrant and endemic biota of Neantarctic South America probably represents survivors which moved north from Antartica before that continent’s glaciation. By the middle Tertiary, mountain building, desertification, and coid climatic pulses had isolated the Neantarctic Realm all along its eastern and northern boundaries, so that its biota has evolved in isolation for perhaps the last 40 million years. Lack of biotic continuity between Neantarctic semideserts and the spatially adjacent North Chilean and Peruvian Coastal Desert seems hard to explain. How Southern Antofagasta Province between 24-24 degrees south is extremely dry and is occupied by several mountain chains averaging 2-3000 m in altitude and extending almost to the coast. This is the only barrier of its kind along Pacific South America between the equator and Tierra del Fuego. During later Tertiary and Pleistocene coid periods, these mountains must have been glaciated, or both very coid and very dry, so that the Neantarctic biota could retreat no farther north at times of clima-deterioration from other South American lineages, locked by physical and climatic barriers into a narrow strip along the Pacific Coast and west of the Andes between Tierra del Fuego and Antofagasta.